Pak-Iran Relations in the Post-Imperial World - Dr. Lubna Abid Ali (Journal of Political Studies, 2009)
The continuing interaction between the peoples of Iran and Pakistan is centuries old. It has its roots in historical, cultural and lingual affinity. ‘From the time of first sustained Muslim influences’, states Howard Wriggins, ‘the models for political structure and processes as well as religious inspiration and cultural influences came from Iran and not the Arab Middle East.’1 The trajectory of Iran - Pakistan relations has been shared by not only the domestic and regional dynamics but also due to the impact of global correlation of forces. As the title indicates, this paper is an attempt to analyze the situation of Pakistan-Iran relations in the post-imperial world.